Increase of prostaglandin E2 in the reversal of fetal ductal constriction after polyphenol restriction. (5th November 2018) - Vian, I.; Zielinsky, P.; Zílio, A. M.; Schaun, M. I.; Brum, C.; Lampert, K. V.; De Ávila, N.; Baldissera, G.; Klanovicz, T. M.; Zenki, K.; Zurita‐Peralta, J.; Olszewski, A.; et al.
ABSTRACT: Objective: Anti‐inflammatory substances that inhibit the synthesis of prostaglandins, such as non‐steroidal anti‐inflammatory drugs (NSAIDs) and polyphenol‐rich foods, can cause constriction of the fetal ductus arteriosus. This study aimed to test the hypothesis that reversal of fetal ductal constriction after maternal restriction of polyphenol‐rich foods, in the third trimester of pregnancy, is accompanied by increased plasma levels of prostaglandin E2 (PGE2). Methods: This was a controlled clinical trial of women with singleton pregnancy ≥ 28 weeks undergoing fetal echocardiography. The intervention group included pregnancies with diagnosis of fetal ductal constriction and not exposed to NSAIDs. The control group consisted of third‐trimester normal pregnancies. Both groups answered a food frequency questionnaire to assess the amount of total polyphenols in their diet, underwent Doppler echocardiographic examination and had blood samples collected for analysis of plasma levels of PGE2. Intervention group participants received dietary guidance to restrict the intake of polyphenol‐rich foods. The assessments were repeated after 2 weeks in both groups. Results: Forty normal pregnancies were assessed in the control group and 35 with fetal ductal constriction in the intervention group. Mean maternal age (26.6 years) and mean body mass index (30.12 kg/m 2 ) were similar between the two groups. Intragroup analysis showed that dietary guidance reduced the median consumption of polyphenols (from 1234.82 to 21.03 mg/day, P  < 0.001), increasing significantly the plasma concentration of PGE2 (from 1091.80 to 1136.98 pg/mL, P  < 0.05) in the intervention group after 2  weeks. In addition, Doppler echocardiography showed reversal of fetal ductal constriction in the intervention group. No significant changes were observed in the control group. Conclusions: Dietary intervention for maternal restriction of polyphenol‐rich foods in the third trimester of pregnancy is accompanied by increase in plasma levels of PGE2 and reversal of fetal ductal constriction. Copyright © 2017 ISUOG. Published by John Wiley & Sons Ltd.